Density and diversity of diazotrophic bacteria isolated from Amazonian soils using N-free semi-solid media (Scientia Agricola, 2011)
Non-symbiotic diazotrophic bacteria are amongst the most important functional groups of soil-dwelling microorganisms. These bacteria contribute to plant growth predominantly through biological N2 fixation. Here, we evaluated the density and diversity of non-symbiotic diazotrophic bacteria in soils taken from diverse land use systems (LUS) in Amazonia using nitrogen-free media. A total of 30 soil samples were collected from the following LUS: pristine forest, young secondary forest, old secondary forest, agroforestry, agriculture and pasture. Bacterial density was evaluated by the most probable number (MPN) method utilizing N-free semi-solid media with varied compositions (JNFb, NFb, LGI and Fam). Individual isolates were characterized by colony and cellular morphology as well as total protein profiles and nitrogenase activity. Isolate genotypes were determined by partial 16S rDNA sequences. No typical diazotrophic growth in the JNFb medium was observed. Bacterial densities in the NFb medium were higher in the agriculture and agroforestry soil samples. In LGI and Fam media, bacterial densities were highest in the pasture soil samples. Overall, 22 isolates with high phenotypic diversity were obtained. Eleven isolates exhibited nitrogenase activity. Sequences of 16S rDNA genes of 14 out of 19 isolates had similarities below 100 % with known nitrogen-fixing species. Isolates were identified as belonging to the Burkholderia, Enterobacter, Serratia, Klebsiella, and Bacillus genera. A higher number of isolates from pasture soil samples were isolated, with the majority of these belonging to the Burkholderia and Bacillus genera. Among the isolates, unknown sequences were obtained, possibly indicating new species. Taken together, these data demonstrate that Fam, NFb, and LGI semi-solid media allowed the growth of diazotrophic bacteria belonging to different phylogenetic lines.